2022
DOI: 10.1038/s41746-022-00613-w
|View full text |Cite|
|
Sign up to set email alerts
|

Prostate cancer therapy personalization via multi-modal deep learning on randomized phase III clinical trials

Abstract: Prostate cancer is the most frequent cancer in men and a leading cause of cancer death. Determining a patient’s optimal therapy is a challenge, where oncologists must select a therapy with the highest likelihood of success and the lowest likelihood of toxicity. International standards for prognostication rely on non-specific and semi-quantitative tools, commonly leading to over- and under-treatment. Tissue-based molecular biomarkers have attempted to address this, but most have limited validation in prospectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…The data involved pathology samples from 5,654 trial patients with high and sufficient quality digital histopathology image data. The results confirmed that artificial intelligence model did outperform traditional clinical risk stratification for predicting outcome, therefore improvements in personalization strategies will help identify patients who could benefit from augmented therapy and potentially titrate therapy for those with favorable features (35).…”
Section: Genomic and Molecular Applications: Current Clinical Usesupporting
confidence: 52%
See 1 more Smart Citation
“…The data involved pathology samples from 5,654 trial patients with high and sufficient quality digital histopathology image data. The results confirmed that artificial intelligence model did outperform traditional clinical risk stratification for predicting outcome, therefore improvements in personalization strategies will help identify patients who could benefit from augmented therapy and potentially titrate therapy for those with favorable features (35).…”
Section: Genomic and Molecular Applications: Current Clinical Usesupporting
confidence: 52%
“…Prolaris, Decipher, and Oncotype genomic profiling testing are available to patients to help define molecular signaling that may suggest a different disease process than implied by traditional biomarkers and tools used to assign risk. In the future, next generation sequencing may be used to complement more traditional biomarkers defined on immunohistochemical staining including markers for neuroendocrine expression (33)(34)(35).…”
Section: Genomic and Molecular Applications: Current Clinical Usementioning
confidence: 99%
“…Additionally, while the usage of artificial intelligence is still an NCCN category IIB recommendation at this time for aiding with risk stratification, new studies suggest it will have an increasing role in cancer therapy precision [8,71].…”
Section: Prostate Genomicsmentioning
confidence: 99%
“…Genomic classifiers and artificial intelligence-based tools using digital histopathology may provide additional guidance. 5,6 PRESTO focused on patients that had progressed biochemically despite maximal local therapy to the pelvis, including salvage radiotherapy. 7 In this setting, intermittent ADT is a standard of care (SoC).…”
Section: Prostate Cancermentioning
confidence: 99%